2021
DOI: 10.3390/md19080446
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments on the Synthesis and Bioactivity of Ilamycins/Rufomycins and Cyclomarins, Marine Cyclopeptides That Demonstrate Anti-Malaria and Anti-Tuberculosis Activity

Abstract: Ilamycins/rufomycins and cyclomarins are marine cycloheptapeptides containing unusual amino acids. Produced by Streptomyces sp., these compounds show potent activity against a range of mycobacteria, including multidrug-resistant strains of Mycobacterium tuberculosis. The cyclomarins are also very potent inhibitors of Plasmodium falciparum. Biosynthetically the cyclopeptides are obtained via a heptamodular nonribosomal peptide synthetase (NRPS) that directly incorporates some of the nonproteinogenic amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 93 publications
0
11
0
1
Order By: Relevance
“…HR37v), similar to that of rifampicin [199]. The anti-tuberculosis activity results from the binding of the peptides to the N-terminal domain of the bacterial protease-associated unfoldase ClpC1, resulting in cell death [192,200].…”
Section: Bacteria-produced Cyclic Peptidesmentioning
confidence: 95%
See 3 more Smart Citations
“…HR37v), similar to that of rifampicin [199]. The anti-tuberculosis activity results from the binding of the peptides to the N-terminal domain of the bacterial protease-associated unfoldase ClpC1, resulting in cell death [192,200].…”
Section: Bacteria-produced Cyclic Peptidesmentioning
confidence: 95%
“…Rufomycin A (102) and rufomycin B (103) have been reported to be highly active against Mycobacterium smegmatis, at 0.2 µg/mL and 0.5 µg/mL, respectively, and M. tuberculosis, at 0.1-0.4 µg/mL and 1-5 µg/mL, respectively, and also against strains resistant to other antibiotics (kanamycin, streptomycin, neomycin, and isonicotinic acid hydrazide). In addition, no significant toxicity was observed on four-week-old mice with intraperitoneal injection of 102 (LD 0 200 mg/kg and LD 100 360 mg/kg) [192]. In another study, rufomycin NBZ8 (104) was found to be the most active peptide, with an MIC of 0.02 µM (M. tuber.…”
Section: Bacteria-produced Cyclic Peptidesmentioning
confidence: 95%
See 2 more Smart Citations
“…In a review by Kazmaier and Junk [ 3 ], cycloheptapeptides molecules as ilamycins, rufomycins, and cyclomarins, including unusual amino acids with important biological activities, are treated. These substances are specifically active against a range of mycobacteria with no significant activity towards other Gram-positive and Gram-negative bacteria or fungi.…”
mentioning
confidence: 99%